Auto-HPGe, an autosampler for gamma-ray spectroscopy using high-purity germanium (HPGe) detectors and heavy shields. (October 2018) - Carvalho, Matheus C.; Sanders, Christian J.; Holloway, Ceylena
Graphical abstract: Abstract: Radionuclide measurements have proven to be essential for determining processes related to pressing environmental issues as well as reconstructing historical events related to natural and anthropogenic activities. The detection of radionuclide tracers in environmental and geological samples provides unique and essential insights into specific sources and sinks. Despite its usefulness in measuring natural and anthropogenic radioisotopes, high-purity germanium (HPGe) gamma ray detectors are rarely automated as a result of the heavy shielding required to use this equipment. Consequently, the commonly available autosamplers for this kind of analysis can be very expensive, exceeding AU400, 000. Here we present auto-HPGe, an autosampler for gamma ray detection in heavy shields that costs about AU1100 to build. Auto-HPGe has potential to make HPGe analysis more attractive to scientists, especially when the equipment is located in remote locations or when the ability to change samples at odd hours is limited.